Comparison of Transcranial Color‐Coded Real‐time Sonography and Contrast‐Enhanced Color‐Coded Sonography for Detection and Characterization of Intracranial Arteriovenous Malformations. (1st February 2014) - Wang, Li-Shu; He, Wen; Wang, Hao; Zhao, Yuan-Li; Tian, Feng-Lan; Ning, Bin; Gao, Jing
Abstract : Objectives: To compare the diagnostic value of transcranial color‐coded real‐time sonography and contrast‐enhanced color‐coded sonography in detection and characterization of intracranial arteriovenous malformations. Methods: Thirty‐one patients highly suspected to have an intracranial arteriovenous malformation were imaged with real‐time and contrast‐enhanced sonography. With digital subtraction angiography as the reference standard, the ability to detect the malformations and accurately determine their size and location was compared between the two imaging techniques. Results: One cavernous hemangioma and 30 intracranial arteriovenous malformations were imaged with real‐time and contrast‐enhanced sonography, which were confirmed by angiography. The detectability of contrast‐enhanced sonography, especially for optimizing visualization of malformations located in the frontal, parietal, and occipital lobes, was higher than that of real‐time sonography, although the overall number of malformations was too small to demonstrate significance. The sizes of the malformations (6 in the frontal lobe, 1 in the parietal lobe, and 1 in the occipital lobe) were underestimated by real‐time sonography compared to angiography, whereas there was agreement in the sizes between contrast‐enhanced sonography and angiography. The detection rates for the 30 arteriovenous malformations on contrast‐enhanced and real‐time sonography were 96.7% (29 of 30) and 70.0% (21 of 30), respectively ( P = .008). Moreover, contrast‐enhanced sonography was significantly superior to real‐time sonography for detection of feeding arteries (59.5% [22 of 37] versus 83.7% [31 of 37]; P = .004). Although the feeding arteries showed increased peak systolic and end‐diastolic velocities after contrast agent injection, there were no statistically significant differences in the velocities before and after injection. Conclusions: Transcranial contrast‐enhanced color‐coded sonography is superior to color‐coded real‐time sonography for detection of intracranial arteriovenous malformations, particularly for lesions located in the frontal, parietal, and occipital lobes of the brain.